HUBUNGAN ANTARA PENGETAHUAN IBU TENTANG TANDA KECUKUPAN ASI DENGAN KEBERHASILAN PEMBERIAN ASI EKSKLUSIF - Rokhmah Ayu Suliasih, NIM011411233007 (2018)
Background: Exclusive breastfeeding (EB) was the most effective intervention for preventing metabolic disease and have an important role for children’s health and growth. Unfortunately, most of developing countries had a low exclusive breastfeeding. Mother’s perception in having insufficient breastmilk was the main reason for stopping breastfeeding and give an extra food in early age. The definition of EB was giving only breastmilk to infants from early birth up to six months, yet medications and vitamin were the exception. This study aimed to examine mother’s knowledge about the sign of breastmilk sufficiency and their sociodemographic, which influencing EB. Method: This cross-sectional study collected 82 mothers of 6 to 11 months baby by consecutive sampling and using questionnaire. Simomulyo and Manukan Kulon public health services in Surabaya were chosen as study’s location. SPSS v22 was used to analyse with chi -square for bivariate and multiple logistic regression for multivariate. Result: Mother’s knowledge about the sign of breastmilk sufficiency did not correlate with EB. Mother’s characteristic which correlated to exclusive breast feeding were age (p=0,020; OR=16,042), mother’s occupation (p=0,003; OR=23,809), formal education (p=0,030; OR=20,833), and exclusive breastfeeding experiences (p=0,032; OR=10,054). Conclusion: There is a relationship between mother’s age, occupation, formal education, and exclusive breastfeeding experiences with EB. Better supporting working-mothers, encouraging behavioural change, and increasing the utilization of antenatal and postnatal counselling (primipara and working mother as the priority) are including to recommendation for having EB.